Exploring differences in the utilization of the emergency department between migrant and non-migrant populations: a systematic review - Giulia Acquadro-Pacera; Martina Valente; Giulia Facci; Bereket Molla Kiros; Francesco Della Corte; Francesco Barone-Adesi; Luca Ragazzoni; Monica Trentin (BMC, 2024)
Abstract Background Migrants face several barriers when accessing care and tend to rely on emergency services to a greater extent than primary care. Comparing emergency department (ED) utilization by migrants and non-migrants can unveil inequalities affecting the migrant population and pave the way for public health strategies aimed at improving health outcomes. This systematic review aims to investigate differences in ED utilization between migrant and non-migrant populations to ultimately advance research on migrants' access to care and inform health policies addressing health inequalities. Methods A systematic literature search was conducted in March 2023 on the Pubmed, Scopus, and Web of Science databases. The included studies were limited to those relying on data collected from 2012 and written in English or Italian. Data extracted included information on the migrant population and the ED visit, the differences in ED utilization between migrants and non-migrants, and the challenges faced by migrants prior to, during, and after the ED visit. The findings of this systematic review are reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Results After full-text review, 23 articles met the inclusion criteria. All but one adopted a quantitative methodology. Some studies reported a higher frequency of ED visits among migrants, while others a higher frequency among non-migrants. Migrants tend to leave the hospital against medical advice more frequently than the native population and present at the ED without consulting a general practitioner (GP). They are also less likely to access the ED via ambulance. Admissions for ambulatory care-sensitive conditions, namely health conditions for which adequate, timely, and effective outpatient care can prevent hospitalization, were higher for migrants, while still being significant for the non-migrant population. Conclusions The comparison between migrants' and non-migrants' utilization of the ED did not suggest a clear pattern. There is no consensus on whether migrants access EDs more or less than non-migrants and on whether migrants are hospitalized at a higher or lower extent. However, migrants tend to access EDs for less urgent conditions, lack a referral from a GP and access the ED as walk-ins more frequently. Migrants are also discharged against medical advice more often compared to non-migrants. Findings of this systematic review suggest that migrants' access to care is hindered by language barriers, poor insurance coverage, lack of entitlement to a GP, and lack of knowledge of the local healthcare system.